White Light-Emitting Diode Coated with K3Lu(PO4)2: Tb3+, Eu3+ Nanocrystal Films Enveloped by SiO2 - Nguyen Van Dung; Nguyen Huy Khiem; Phan Xuan Le (International Journal of Technology)
A series of novel adjustable-illumination including K3Lu(PO4)2: Tb3+, and Eu3+ (KLPO:Tb,Eu) phosphors with improved energy-transfer efficiency were made using strong-heat solid-state (SS) reactivity. X-ray diffractivity (XRD), luminescence spectroscopy, chromatic coordination, and fluorescence decomposition analyses were used to describe the materials. The first-principles method during the analysis was used to investigate power band structure as well as denseness for statuses in K3Lu(PO4)2. The result showed that the doping dose ratio for Tb3+/Eu3+ was found to be the main factor controlling the energy transmission (ET) between Tb3+ and Eu3+ elements. The ET between Tb-Eu was governed by an electric dipole-dipole interaction which produced tunable emissions from green to orange-red regions. During the study, a 365 nm chip was incorporated with BaMgAl10O17: Eu2+ blue phosphor, SiAlON:Eu2+ green phosphor, and K3Lu(PO4)2:0.1Tb3+,0.06Eu3+ (KLPO:0.1Tb,0.06Eu) orange-red phosphor to create a triple-phosphor-based white light-emitting diode (WLED). The device generated white light featuring a great chroma rendition indicator reaching 91.4 as well as an acceptable associated chroma temperature reaching 3678 K. These properties showed that the developing phosphor was suitable for warm WLED applications, as the performance was comparable to those of perfect white light.